CURRENT STATE AND DEVELOPMENT PROSPECTS OF THE HOTEL INDUSTRY OF UKRAINE - Pohrebniak, A. V.; Yazina, V. A.; Naumovych, T. R. (Systems and Technologies, 2022)
The article identifies the main negative factors of the impact of the «lockdown» and sanitary-hygienic, epidemiological measures, and the adaptation resources used by the hotel business to minimize (or prevent) them in order to optimize functioning. Throughout the entire evolutionary history of homo sapiens, man had to, and therefore sought, to satisfy his primary needs, guided by the instinct of self-preservation. In order to achieve this goal, in search of suitable conditions for existence, it covered huge distances on the land of our planet. Large "dispersals of peoples", quite well researched by scientists, were always accompanied by migration processes of small population groups of certain territories (families, tribes, etc.), which led, thanks to the exclusive adaptive properties of man as a species, to its maximum spread over the entire surface of the Earth. The range of needs of a modern person, who is mostly urbanized (in the economically developed countries of the EU, North America, and Southeast Asia, the degree of urbanization of the population varies between 70 and almost 100 percent), today, of course, is not limited to the first and second rungs of Maslow’s ladder, but extends to the maximum its high tiers, which can be provided with a valid technological resource. Modern technological development of the developed countries of the world can also ensure almost unlimited use of the adaptive resource of each person traveling in his needs for movement between the points of this trip, for whatever purpose it is carried out. The tourism sector of the economy of Ukraine, which is not fully evaluated, deserves more and more attention, which is able to cause a multiplicative and synergistic effect not only in the development of the hotel and restaurant business, retail, and the service sector, but also to become a significant contribution to the economy of the entire country. More than 1,600 hotels in Ukraine provided more than 400,000 jobs as of 2019, the hospitality market in terms of profitability and profitability, revenues to the state budget, return on investments and projects, the tourism industry still occupies a leading position in the economy of Ukraine. The state of the tourism industry is an important indicator of the investment climate in the country, and the hotel industry is the main determinant.